KCNJ2 Facilitates Clear Cell Renal Cell Carcinoma Progression and Glucose Metabolism - Qiyue Zhao; Zhengshu Wei; Guanglin Yang; Liwei Wei; Hao Chen; Zelin Cui; Naikai Liao; Min Qin; Jiwen Cheng (International Journal of Genomics)
Conclusion: KCNJ2 plays a crucial role in ccRCC progression through affecting glucose metabolism and immune responses. Our findings reveal the functional role of KCNJ2 in promoting tumor progression and metabolic reprogramming in ccRCC, highlighting its therapeutic potential as a novel target for ccRCC treatment. Further studies are essential to clarify the mechanisms by which KCNJ2 affects ccRCC biology and to evaluate its clinical relevance.